2020
DOI: 10.5765/jkacap.190035
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Attempts and Contributing Factors among South and North Korean-Family Youth Using the Korean Youth Risk Behavior Web-based Survey

Abstract: Objectives: There is an increasing number of North Korean adolescents in South Korea. These adolescents need clinical attention as they experience a high risk of suicidal behavior because of the childhood adversity and acculturative challenges that they face before and after arriving in South Korea. This study assessed the risk of suicide attempts among North Korean adolescents compared to South Korean adolescents, and investigated the contributing factors for each group. Methods: We used data from the Korean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Five studies investigated the influence of educational attainment on suicide attempts; three of them only included adults [ 36 , 38 , 41 ], two covered the age group of adolescents [ 5 , 62 ]. The level of education was measured by the number of educational years, the educational graduation, or rather the last school the subjects have attended.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies investigated the influence of educational attainment on suicide attempts; three of them only included adults [ 36 , 38 , 41 ], two covered the age group of adolescents [ 5 , 62 ]. The level of education was measured by the number of educational years, the educational graduation, or rather the last school the subjects have attended.…”
Section: Resultsmentioning
confidence: 99%
“…When comparing college education with middle or high school educational levels, the association was found to be strongly attenuated. Neither mother’s or father’s education was significantly associated with suicide attempts in the study by Rim et al [ 62 ], which compared the risk factors between South- and North-Korean adolescents. Ki et al [ 36 ] observed that educational attainment was found to have the largest indirect effect (through increasing the risk for physical illness and problem drinking) for attempted suicide of all investigated variables such as income or occupation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The country has been known for its persistently high suicide deaths over the past decade (OECD, 2019). Although national statistics for suicide rates among North Korean (NK) refugees have not been reported, recent reports on mental health among them show that they are at greater risk for suicide than the general population (Rim et al, 2020;Um et al, 2020). According to the Korea Hana Foundation (2019), more than 12% of NK refugees in South Korea had desired or attempted to commit suicide in the previous 12 months.…”
Section: Introductionmentioning
confidence: 99%
“…Translational research also takes place in terms of culture and research subjects. In Subin Park's "Suicide attempts of South and North Korean-family youth and contributing factors using the Korean youth risk behavior web-based survey," the study involved adolescents who had parent(s) of North Korean origin, rarely exposed to clinical research [9]. Eunjoo Kim's "The use of virtual reality in psychiatry: a review" introduced a training program that enhances the attention span, academic skill, and social adaptability in a virtual classroom situation [10].…”
mentioning
confidence: 99%